2018
DOI: 10.1111/jfb.13858
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of settlement‐stage reef fishes captured by light‐trap in a tropical south‐west Atlantic Ocean coastal reef system

Abstract: This study reports the results of 5 years of monitoring reef fish post‐larvae using light traps in the Bay of Tamandaré, north‐east Brazil. An annotated checklist of pre‐settlement fish species, their frequency of occurrence and taxonomic characteristics are provided. In total, 4,422 post‐larval fishes belonging to 36 families, 56 genera and 76 species were captured. The most species‐rich families were Carangidae (7), Lutjanidae (6) and Pomacentridae (4), while the families Gerreidae (30.47%), Holocentridae (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 102 publications
(120 reference statements)
0
6
0
1
Order By: Relevance
“…We observed an over-evaluation of species richness when using only morphological characters, 571 morphospecies vs. 387 species when using DNA barcoding combined with a morphological approach. Inversely in other studies, using only a morphological approach has also led to an underestimation of the number of species as observed by [13] in the southwest tropical Atlantic Coast. These authors identified 76 post-larval reef fish morphospecies from 465 samples (i.e., the catches of one light trap for one night) over five years by using morphological and meristic characteristics.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…We observed an over-evaluation of species richness when using only morphological characters, 571 morphospecies vs. 387 species when using DNA barcoding combined with a morphological approach. Inversely in other studies, using only a morphological approach has also led to an underestimation of the number of species as observed by [13] in the southwest tropical Atlantic Coast. These authors identified 76 post-larval reef fish morphospecies from 465 samples (i.e., the catches of one light trap for one night) over five years by using morphological and meristic characteristics.…”
Section: Discussionmentioning
confidence: 85%
“…Obtaining the precise Diversity 2022, 14, 377 2 of 13 species richness in early life stages of fish remains, therefore, challenging [7]. For this reason, most previous studies describing larval fish diversity remain limited to the family level in temperate and tropical areas [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Species captured only by trawls were mostly those considered scarce and rare. However, their detection is important, as rarity is a common feature in reef fish communities and they might be highly important in the ecosystem despite they are not the most abundant or frequent (Grande et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These challenges are well‐addressed in this issue of JFB where we feature an exemplary, richly illustrated study by Grande et al . () of settlement‐stage reef fish post‐larvae from the Bay of Tamandare in northeastern Brazil.…”
mentioning
confidence: 99%